The Diversity of Medicinal Plants Planted as Ornamental and Shade Plants - Ratnani, Dewa Ayu Sri (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aimed to identify the diversity of medicinal plants planted as ornamental and shade plants and to determine the plant diversity index on the campus of Universitas Mahasaraswati (UNMAS) Denpasar. Data were collected using an exploration survey and data collection techniques using the cruising technique. The results documented 154 species, 122 genera spread across 54 families. The largest families are Araceae (21), followed by Asparagaceae (12) and Acanthaceae (8). As many as 146 species (94.8%) of 154 species were found to be medicinal plants. The largest species was dominated by Hymenocallis littoralis (Jacq.) Salisb. The shrub level category was the highest (64), followed by herbs (57) and trees (33). The diversity index value of H’ = 5.622, which is included in the high category. The diversity index values ​​at each level include shrubs = 3.52 (high), herbs = 3.383 (high), and trees = 2.759 (medium).